Changes of selected hematological parameters and morning rest rate during ten days high altitude stay and training - Suchý, J.; Pernica, J.; Korvas, P. (AUC Kinanthropologica, 2014)
Changes of Selected Hematological Parameters and Morning Rest Rate during Ten Days High Altitude Stay and Training This article describes the influence of a ten day stay and training in a high altitude area (1850 m ASL) on selected blood count parameters and morning resting heart rate. Three tests were performed on a group of young cross country skiers (n = 10, age: 18.7 ± 4.8): two days before, two days after and ten days after the altitude training camp. Two day after the return, significant (p < 0.05) increases in hemoglobin level (5.4%), red blood cell (3.2%) and hematocrit (4.3%) were observed. Ten days after the return to the lowland, were found significant increases in concentration of hemoglobin and red blood cell (p < 0.05) compared with the check measurement before high altitude. Increases in hematocrit were not significant. The heart rate was higher during the camp than before (p < 0.01). The average decrease in heart rate (2.6%) ten days after the return in comparison with basal data was not statistically significant (p > 0.05). The study in a group of young cross country skiers has shown positive effects of a tenday training camp in high altitude on blood count parameters and morning resting heart rate monitored in lowland two and ten days after the return from high altitude.